2021
DOI: 10.7150/jca.54699
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Reactive Oxygen Species and their Application in Cancer Therapy

Abstract: Reactive oxygen species (ROS) play a dual role in the initiation, development, suppression, and treatment of cancer. Excess ROS can induce nuclear DNA, leading to cancer initiation. Not only that, but ROS also inhibit T cells and natural killer cells and promote the recruitment and M2 polarization of macrophages; consequently, cancer cells escape immune surveillance and immune defense. Furthermore, ROS promote tumor invasion and metastasis by triggering epithelial-mesenchymal transition in tumor cells. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 185 publications
(255 reference statements)
3
62
0
Order By: Relevance
“…Consistent with the studies on the relationship of iron and GC, ferroptosis has also been found to be closely related to the proliferation, invasion, and metastasis in GC ( Chen et al, 2021a ; Huang et al, 2021 ). However, the predictive role of ferroptosis in GC remains elusive ( Shao et al, 2021 ).…”
Section: Ferroptosis In Gastric Cancersupporting
confidence: 85%
“…Consistent with the studies on the relationship of iron and GC, ferroptosis has also been found to be closely related to the proliferation, invasion, and metastasis in GC ( Chen et al, 2021a ; Huang et al, 2021 ). However, the predictive role of ferroptosis in GC remains elusive ( Shao et al, 2021 ).…”
Section: Ferroptosis In Gastric Cancersupporting
confidence: 85%
“…Cancer cells contain high basal ROS levels, which cause sensitizes cells to excessive oxidative stress. Therefore, excessive ROS are also deadly to osteosarcoma cells [62] . Research has indicated that multiple chemotherapeutic agents induce apoptosis and autophagy in tumor cells through ROS generation [30] .…”
Section: Discussionmentioning
confidence: 99%
“…7 ). ROS play a bidirectional role either in the initiation and development or in the suppression and treatment of cancer [ 62 – 64 ]. Several studies supported the effect of ROS production on the initiation, progression, and metastasis of several types of tumors.…”
Section: Discussionmentioning
confidence: 99%